2014
DOI: 10.5846/stxb201306091509
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal and environmental control on evapotranspiration in a plantation in the lower mountain areas of North China

Abstract: 摇 摇 摇 摇 摇 摇 摇 渊 杂匀耘晕郧栽粤陨 载哉耘月粤韵冤 摇 摇 第 猿源 卷 第 猿 期摇 摇 圆园员源 年 圆 月摇 渊 半月刊冤 目摇 摇 次 前沿理论与学科综述 灾后生态恢复评价研究进展 刘孝富袁王文杰袁李摇 京袁等 渊缘圆苑冤 噎噎噎噎噎噎噎噎噎噎噎噎噎噎噎噎噎噎噎 基于生态能量视角的我国小水电可持续性分析 庞明月袁张力小袁王长波 渊缘猿苑冤 噎噎噎噎噎噎噎噎噎噎噎噎噎 个体与基础生态 北部湾北部海域夏季微型浮游动物对浮游植物的摄食压力 马摇 璐袁曹文清袁张文静袁等 渊缘源远冤 噎噎噎噎噎噎 鲶鱼和胡子鲶的两性异形与雌性个体生育力 樊晓丽袁林植华袁丁先龙袁等 渊缘缘缘冤 噎噎噎噎噎噎噎噎噎噎噎噎 环境温度对白头鹎代谢产热和蒸发失水的影响 林摇 琳袁曹梦婷袁胡益林袁等 渊缘远源冤 噎噎噎噎噎噎噎噎噎噎噎 灌溉对沙拐枣幼苗生长及氮素利用的影响 黄彩变袁曾凡江袁雷加强袁等 渊缘苑圆冤 噎噎噎噎噎噎噎噎噎噎噎噎噎 孕粤匀泽 污染土壤植物修复对酶活性的影响 朱摇 凡袁洪湘琦袁闫文德袁等 渊缘愿员冤 噎噎噎噎噎噎噎噎噎噎噎噎噎 基于修正 砸陨杂运耘 模型的重庆岩溶地区地下水脆弱性评价 魏兴萍袁蒲俊兵袁赵纯勇 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Ω was similar to that in some other broadleaved forests (Wilson & Baldocchi, 2000) but larger than that in some coniferous forests (Humphreys et al, 2003). Many studies have showed that Ω and g s in dry period are significantly lower than that in abundant water period (Huang et al, 2014). Year 2019 was a typical dry year (Figure 3c–e); Ω and g s in 2019 were significantly lower than those in 2017 and 2018 (Figures 3g and 6a).…”
Section: Discussionmentioning
confidence: 99%
“…The Ω was similar to that in some other broadleaved forests (Wilson & Baldocchi, 2000) but larger than that in some coniferous forests (Humphreys et al, 2003). Many studies have showed that Ω and g s in dry period are significantly lower than that in abundant water period (Huang et al, 2014). Year 2019 was a typical dry year (Figure 3c–e); Ω and g s in 2019 were significantly lower than those in 2017 and 2018 (Figures 3g and 6a).…”
Section: Discussionmentioning
confidence: 99%